Do pop-up ads in online videogames influence childrenâs inspired-to behavior? - Abbasi, A.Z. (Emerald Group Holdings Ltd., 2021)
Purpose: Advertising through the videogame has become one of the most effective and prevalent channels of advertisement, especially via pop-up ads â appearing on the screen that interrupts childrenâs gaming activity. Despite its importance, the effectiveness of pop-up ads and its advertising value in online videogames (O-VGs) to predict childrenâs inspired-to behavior remains scant. This study aims to investigate the underlying factors that explain the relationship between the four dimensions of pop-up ads and perceived advertising value, which further predicts childrenâs inspired-to behavior. Design/methodology/approach: Data from 196 parents who observed their children while playing O-VGs, were analyzed using Smart-PLS. As the respondents are parents, the authors took extra precautions to ensure that the findings are valid. Findings: Results showed that perceived irritation and incentives of pop-up ads do not affect childrenâs advertising value, whereas perceived informativeness and entertainment of pop-up ads positively impact perceived advertising value among children. Besides, childrenâs perceived advertising value of pop-up ads in O-VGs predict their inspired-to behavior. Originality/value: This study contributes to childrenâs inspired-to behavior via empirically studying the perceived advertising value as a potential deriving source of inspiration. Finally, the study provides information for developers/advertisers about why and under what circumstances children perceived advertising value affect inspired-to behavior. Â© 2021, Emerald Publishing Limited.